Between Elitism and Egalitarianism: the Heritage Tram Line in Wrocław as an Example of a Search for an Acceptable Tourist Product - Krzysztof Kołodziejczyk (Tourism, 2020)
The Heritage Tram Line is one of the tourist attractions of Wrocław. It is a way of making use of a large and diverse collection of historic trams that illustrate the development of public transport in the capital of Lower Silesia and, more broadly, in Central Europe. Although it has been operating since 2009, in recent years major modifications have been introduced including increasing the number of routes, a guided commentary on selected journeys, diversifying the historic tram cars and changing the ticket prices. The aim of the article is to evaluate these changes from the perspective of the interest of its users. The data on the frequency of operation and sales of tickets in the 2019 season have been analysed and compared with data from the previous year. This takes into account the increase in availability of the offer, as a consequence of a considerable reduction in ticket prices and introducing a larger number of stops, which has made the Heritage Tram Line more similar to a regular one. The changes introduced have resulted in a greater number of passengers, but also lower revenues as well as certain organisational problems such as ensuring the quality of guided services when passengers are being exchanged at intermediate stops. These issues are considered in the context of how to design a tourist product.